2017
DOI: 10.1007/s12552-017-9207-z
|View full text |Cite
|
Sign up to set email alerts
|

Differences Between African Americans and Non-Hispanic Whites Utilization of Clergy for Counseling with Serious Personal Problems

Abstract: There is a paradox in research on African Americans and non-Hispanic whites in the utilization of clergy. Research finds that African Americans have higher levels of religious service attendance and higher levels of contact with clergy. Research also finds that despite this, African Americans are less likely than non-Hispanic whites to seek out assistance from clergy for psychiatric disorders including depression and anxiety. The goal of this paper was to investigate race differences in the use of clergy for c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 38 publications
0
30
0
Order By: Relevance
“…In addition, because African Americans have more contact with clergy (Krause & Batisda, 2011); and are more likely to see them as a member of their social network, they may be less likely to discuss personal problems such as marital issues. Chatters et al, (2017) results reveal that seeking assistance from clergy is much more nuanced than previously thought. Their paper builds upon previous research on the use of clergy (Chatters et., 2011; Mattis et al, 2007; Neighbors et al, 1998; Taylor et al, 2011; Taylor et al, 2004; Wang et al, 2003).…”
mentioning
confidence: 74%
See 2 more Smart Citations
“…In addition, because African Americans have more contact with clergy (Krause & Batisda, 2011); and are more likely to see them as a member of their social network, they may be less likely to discuss personal problems such as marital issues. Chatters et al, (2017) results reveal that seeking assistance from clergy is much more nuanced than previously thought. Their paper builds upon previous research on the use of clergy (Chatters et., 2011; Mattis et al, 2007; Neighbors et al, 1998; Taylor et al, 2011; Taylor et al, 2004; Wang et al, 2003).…”
mentioning
confidence: 74%
“…Two studies in this special issue address religious influences on help-seeking for mental health and other serious problems (Hays & Lincoln, 2017; Chatters et al, 2017). Hays and Lincoln (2017) examine the impact of religious participation on both formal and informal help-seeking for psychiatric disorders among African Americans.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…While masculinity norms could prevent some men from utilizing mental health services [ 13 ], literature into Black men’s help-seeking found that Black men will reach out for help with emotional problems; they are likely to use informal systems of care [ 48 , 49 ]. Thus, some of the Black men with a psychiatric disorder in the current study are likely to have sought mental health assistance from clergy, family or friends, or other informal sources of support [ 14 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 ]. Given the chronic and persisting nature of psychiatric disorders, which has been reported for Blacks more than others [ 6 , 7 ], our findings indicate that Black men’s mental health needs are not being met adequately through these alternate pathways to care.…”
Section: Discussionmentioning
confidence: 99%
“…Churches play an integral institutional role in the narratives of African American communities (Brodsky, ; Taylor et al., ). Not only do churches function as religious organizations, but also they are key institutions for providing important civic, educational, health, and social resources to church members and nonparticipants alike (Chatters et al., ; Mammana‐Lupo, Todd, & Houston, ). As a group, African Americans demonstrate high levels of religious involvement, with 90% attending religious services (outside of weddings and funerals), and among attendees about 70% attend services at least a few times a month (Taylor et al., ).…”
Section: Introductionmentioning
confidence: 99%